General analysis of stressed beams on elastic foundation subjected to discontinuous loads. (3rd April 2017) - Taha, MH
Abstract : Analytical solutions describing the static and dynamic behaviour of axially loaded beams with elastic end restrains resting on two parameter foundation subjected to multiple discontinuous lateral loads have been obtained using the Adomian decomposition method (ADM). Fourier expansion (FE) is used to transform discontinuous loads to continuous loading functions. The effects of the truncation index of both the ADM and FE on the accuracy of the obtained solutions are studied to assess the validity of the given solutions. The influences of end restraints, foundation stiffness, loading type, axial stressing and excitation frequency on the beam deflection and straining actions are investigated. It has been concluded that as the foundation stiffness increases relative to the beam stiffness, the effects of the end conditions on the beam behaviour decrease.